Antimicrobial resistance in Malaysia : a cross-sectional study analysing trends and economic impacts. - Muhammad Nur Amir, AR; Sharifa Ezat, Wan Puteh; Roszita, Ibrahim; Md Mizanur, Rahman; Zulkefly, Abdul Karim; Fawzi Zaidan, Ali; Nor Farah, Bakhtiar (BMJ Publishing Group Ltd., 2025)
Objective This national study assessed the economic impact of treating patients with antimicrobial resistance (AMR) pathogens within Malaysia’s Ministry of Health (MoH) hospitals. Design A cross- sectional study design and top- down costing approach, analysing Malaysian diagnosis- related group (DRG) data for AMR patients admitted to MoH hospitals from 2017 to 2020. Setting and participants A total of 1190 cases were identified using International Statistical Classification of Diseases-10 version 2010 codes for AMR pathogens. Outcome measures The study aims to estimate direct healthcare costs for treating AMR patients. Costs per admission were calculated based on each patient’s length of stay (LOS). A binary logistic regression model identified cost determinants, with significant factors (p<0.05) further analysed using a multivariate multiple logistic regression. ORs with 95% CIs were determined, and treatment costs were categorised as above or below the annual national base rate. Results Findings showed that costs are influenced by the volume of cases identified through DRG codes and LOS, which averaged between 21.7 and 36.4 days. Median admission costs for AMR patients ranged from RM12 476.28 (IQR RM 15 655.93) to RM19 295.11 (IQR RM20 200.28). Both LOS and total costs increased annually, from RM3 711 046.10 in 2017 to RM9 700 249.08 in 2019. Patients over 56 years old and those with severity levels II and III were more likely exceeding the national base rate. Conclusions These findings, explaining 9.3% of the variance in the regression model, can inform policies to reduce the economic burden of AMR and improve patient outcomes, highlighting the need for a comprehensive strategy to address this global health threat.